Covid-19 scenario, Kubler Ross model and the novel "Shehar Khaki, Kocha Khali": A Psychological - Noon, Yousaf; Asghar, Ghulam; Abbas, Tahir (sourcecoder, 2022)
Greif is deeply rooted in psychology. Psychologists have tried to resolve the grief and the psychological complications that arise from it. In order to understand the psychology of grief, Kubler Ross developed a model which presents psychology of grief in stages. These five stages are named as denial, anger, bargaining, depression and acceptance respectively. A grieving man takes turn in all these stages. Almost all the stages can be observed in the novel "Shehar Khaki Kocha Khaki" and the narrator of the story too goes through all these stages. David Kessler adds one more stage which he named finding the meaning. After the acceptance of grief, a patient finds meanings in the darkness of life and gives meaning to his life. Kubler's model opens new doors for understanding Tarar's novel.